Amulet keepers - Northrop, Michael (New York, NY : Scholastic Inc., 2015)
Alex and Ren travel to London to defeat a Death Walker.
5.2
3-6
3-6
690L
Keywords: Death -- Juvenile fiction; Magic -- Juvenile fiction; London (England) -- Juvenile fiction; Death -- Fiction; Magic -- Fiction; London (England) -- Fiction; Adventure and adventurers -- Fiction; Death -- Fiction; Magic -- Fiction; London (England) -- Fiction; Adventure fiction; Adventure fiction